Transoral rigid 70‐degree laryngoscopy in a pediatric voice clinic. (13th December 2018) - Ongkasuwan, Julina; Devore, Danielle; Hollas, Sarah; Yan, Jennifer
Abstract : Objective: Complaints of dysphonia and dysphagia frequently require rigid or flexible laryngoscopy in the office to aid in diagnosis. For young children, flexible laryngoscopy can be uncomfortable and often requires multiple adults to restrain the child. Rigid laryngoscopy does not result in crying but does require patient cooperation; thus, it is used primarily in adults. This project describes our experience using rigid laryngoscopy in a pediatric cohort. Methods: This was a retrospective chart review of patients at a pediatric voice clinic who underwent laryngoscopy from December 2011 through March 2017. Data analysis is via Student t test and descriptive analysis. Results: Three hundred and eleven patients were identified with 423 unique laryngoscopy exams. Of those, 212 of the exams were flexible and 210 were rigid. One patient did not tolerate either rigid or flexible exam. There was a statistically significant difference in age between children diagnosed via rigid mean 10.92 years (range 2.39–19.14 years) versus flexible mean 6.51 years (range 0.41–19.29 years), P ≤ 0.01. Of the 44 children under 3 years of age, flexible laryngoscopy was used almost exclusively, with 43 of 44 (97.7%) flexible scope exams. Rigid laryngoscopy was performed on 24 of 115 (20.9%) children aged 3 to 5 years, 26 of 40 (65%) aged 6 years, and 159 of 223 (71.3%) aged 7 and older. Conclusion: Transoral 70 o rigid laryngoscopy can be used in select children as young as 3 years of age. This modality allows for improved visualization of lesions with greater comfort for patients. Laryngoscope, 129:1657–1659, 2019